STUDENTS’ PERCEPTION OF USING WHATSAPP FOR LEARNING ENGLISH AT SMP ISLAM AS-SHOFA - Sri Wahyuni; Jismulatif; Mahdum (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article examines students’ perceptions of using WhatsApp for learning English at SMP Islam As-Shofa and investigates differences between male and female students’ perceptions. The study employed a quantitative descriptive design involving 30 ninth-grade students from two classes. Data were collected through online questionnaires distributed via a WhatsApp group. Students’ responses were analyzed using a Likert scale to measure perceptions of WhatsApp as a learning tool. The results indicate that WhatsApp is fairly feasible for learning English, with 40% of students expressing a positive perception. Regarding gender differences, 24.4% of male students and 21% of female students reported positive perceptions. Conversely, 45.2% of students expressed negative perceptions, with 23.8% of males and 22.4% of females disagreeing. These findings suggest that while WhatsApp can support English learning, students’ perceptions vary, highlighting the need for strategies to enhance engagement and effectiveness in online learning environments.